Fundamental performance investigation on reactive liquid asphalt. (10th July 2019) - Li, Jiusu; Fan, Yang; Dai, Lingchun; Liu, Jianfang
Abstract: Low initial strength, slow strength increase, slow curing, high temperature susceptibility, poor water damage resistance, and poor storage stability are the major shortcomings of traditional cold mix asphalt (CMA). Unlike the traditional CMA, reactive liquid asphalt (RLA) was produced to overcome the weaknesses in this study. Its optimal ingredient mix, which includes silane coupling agents (SCA), asphalt modifiers, reactive solvents (RS), and curing agents (CA) was determined according to the single factor and orthogonal experimental results in the laboratory. The performance of the resulting RLA was systematically evaluated. The fundamental properties proved favorable, which were characterized by penetration of 5 mm, ductility of 49 cm and softening point of 70 °C, the dynamical shear rheology (DSR) and bending beam rheology (BBR) results showed that its performance grading could reach PG70-22, indicating satisfactory for most regions in the world. The adhesion between RLA and coarse aggregate results suggested that the stripping risk was significantly reduced. In addition, the satisfied compatibility and performance of RLA were revealed by analyzing scanning electron microscopy (SEM) and infrared spectral analysis (IR) results. Graphical abstract: Image 1 Highlights: Petroleum based solvents were not used to liquefy the original bitumen. Reactive liquid asphalt overcomes severe pollution and high energy consumption of HMA. Strength growth is based on reaction of reactive solvent and hydration products of portland cement. Performance grading of reactive liquid asphalt can reach PG70-22.